Genetic and physiological effects of subinhibitory concentrations of oral antimicrobial agents on Streptococcus mutans biofilms: Effects of sodium fluoride and chlorhexidine on Streptococcus mutans - Filho, Jaime Gazola [UNESP]; Vizoto, Natália Leal [UNESP]; Luiza de Aguiar Loesch, Maria [UNESP]; Dias de Sena, Marina [UNESP]; Mendes da Camara, Danielle [UNESP]; Caiaffa, Karina Sampaio [UNESP]; de Oliveira Mattos-Graner, Renata; Duque, Cristiane [UNESP] (Elsevier, 2021)
Streptococcus mutans is the main etiological agent of dental caries because of its capacity to adhere to enamel structure and form biofilms. This study aimed to evaluate the effects of the anticariogenic agents - sodium fluoride (NaF) and chlorhexidine (CHX) - at levels below minimum inhibitory concentrations (sub-MICs) on the growth of planktonic cells and biofilms and on the expression of vicR and covR genes associated with the regulation of biofilm formation. MICs and minimum bactericidal concentrations (MBCs) of NaF and CHX were determined for S. mutans strains ATCC25175, UA159 and 3VF2. Growth curves were constructed for planktonic cells cultured in brain heart infusion (BHI) broth supplemented with NaF (0.125–0.75MIC) or CHX (0.25–0.75MIC). Biofilm formation assays were performed in microplates containing CHX or NaF at 0.5–1.0MIC and stained with violet crystal. Quantitative polymerase chain reaction determined the alterations in covR and vicR expression in cells exposed to antimicrobials at sub-MIC levels. NaF and CHX at sub-MIC levels affected the growth of planktonic cells of all three S. mutans strains, depending on the concentration tested. The biofilm formation in UA159 and 3VF2 was reduced by NaF at concentrations ≥0.5 MIC, while that of ATCC 25175 was reduced significantly irrespective of dose. In contrast, UA159 and 3VF2 biofilms were not affected by CHX at these levels, whereas those of ATCC 25175 were reduced significantly at all concentrations tested. Under sub-MIC conditions, CHX and (to a lesser degree) NaF increased vicR and covR expression in all three strains, although there were large differences between strains and treatment conditions employed. CHX and NaF at sub-MIC levels influence on the growth of S. mutans in planktonic and biofilm conditions and on transcript levels of biofilm-associated genes vicR and covR, in a dose-dependent manner.
Keywords: Biofilms; Chlorhexidine; Fluoride; Gene expression; Streptococcus mutans